Political Conviction and Epistemic Injustice. - Case, Spencer (Philosophia, 2021)
Epistemic injustice occurs when we fail to appropriately respect others as epistemic agents. Philosophers building on the work of Miranda Fricker, who introduced the concept, have focused on epistemic injustices involving certain social categories, particularly race and gender. Can there be epistemic injustice attached to political conviction and affiliation? I argue yes: politics can be a salient social category that draws epistemic injustice. Epistemic injustices might also be intersectional, based on the overlap of politics and some other identity category like race or sex. Further, and more provocatively, I argue that political minorities in academia, in particular conservatives and libertarians, are most likely the victims of epistemic injustice on the basis of their politics. Such epistemic injustices might even be routine. Although more limited in scope and severity than other forms of epistemic injustice, political epistemic injustices in academia ought to be of special concern from a standpoint of social justice because of the academy's central role in knowledge production and dissemination.